Preservasi Musik Keroncong sebagai Genius Product Indonesia - Arifa, Laily Nur (LoroNG: Media Pengkajian Sosial Budaya, 2012)
Keroncong is an Indonesian characteristic musical art that comes from the acculturation of Portuguese and Indonesian culture. One ofthe most famous songs is Bengawan solo that was created by Gesang. But now, keroncong musik suffering a setback. It’s different with Malaysia state. There succeding keroncong musik. So, many European think keroncong musik comes from Malaysia. Certainly, it was opposed by the people of Indonesia. But, behind the claim of, actually, the people of Indonesia have been made aware by the neighboring state about how beautiful our culture. We are required to maintain the culture that is not extinct and taken by other countries. Preservation of keroncong music can be through various means, one of them is efforts to combine pop musik with school, establish the course of keroncong musik, performing keroncong musik, and often socialize pop musik on televisi and other media. Keroncong merupakan kesenian musik khas Indonesia yang berasal dari akulturasi budaya Portugis dan budaya nasional. Salah satu lagu keroncong yang paling fenomenal adalah Bengawan Solo ciptaan Gesang. Namun, kini musik keroncong seakan mati suri. Hal ini berbeda dengan Malaysia. Di sana, keroncong seakan menemukan kembali masa emasnya sehingga banyak warga eropa mengira keroncong adalah kesenian Malaysia. Malaysia sendiri telah mengklaim bahwa keroncong adalah kebudayaan Malaysia.Tentu saja hal ini diprotes keras oleh rakyat Indonesia. Namun dibalik klaim tersebut, sebenarnya rakyat Indonesia telah disadarkan oleh Negara tetangga tentang betapa indahnya budaya kita. Kita dituntut untuk menjaga budaya agar tidak punah dan diambil oleh Negara lain. Pelestarian keroncong dapat melalui berbagai cara, salah satunya ialah de ngan upaya integrasi keroncong dan kurikulum sekolah, mendirikan kursus keroncong, menggelar pentas keroncong hingga sering mensosialisasikan musik keroncong di media.